Notes on Medical Practice in Southern Dalmatia (Testimonies from the Eastern Adriatic Coast and its Hinterland) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper presents testimonies of ancient medical practices in the southern part of the province of Dalmatia. Epigraphic records and archaeological discoveries reveal the presence of physicians and their healthcare practices among the population of southern Dalmatia during Roman rule. Evidence from inscriptions that detail patient care from that era, alongside a limited number of physical artefacts related to medical practice, supports the existence of this tradition. These discoveries hold great historical significance, providing clearer insight and understanding of medical practices in ancient southern Dalmatia.
Keywords: epigraphic evidence; archaeological finds; physician; healing; southern Dalmatia province